PENGARUH PEMBAGIAN TUGAS TERHADAP EFEKTIVITAS KERJA PEGAWAI BAGIAN PERLENGKAPAN SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Dodi Atmaja (ADMINISTRASI PUBLIK, 2019)
The purpose of this study is to determine whether the division of tasks has to do with the work effectiveness of employees in the Equipment Section of the Regional Secretariat of East Kutai Regency.Therefore, the authors obtain an overview of the division of tasks and work effectiveness of employees is very important so that employees better understand in depth about the concept of State Administration in the context of division of tasks in order to support the successful implementation of tasks in the Regional Office of East Kutai Regency.Even though the division of tasks is not the only factor that supports success to create employee work effectiveness, it turns out that the division of labor factors influences the work effectiveness of employees.As the Leader it is suggested that more devote attention to the needs of individual employees, and provide freedom for employees to develop their creativity, and provide broader experience to employees through continuous development activities.And to employees, especially those who were used as respondents in this study, it was suggested that they continue to improve their morale and ability to bring the organization's mission below the tighter level of competition, so that it will be created well, which can simultaneously improve organizational performance in the face of global competition .